Critical-Sized Bone Defects: Sequence and Planning - Toogood, Paul (J Orthop Trauma, 2017)
Bone defects associated with open fractures require a careful approach and planning. At initial presentation, an emergent irrigation and debridement is required. Immediate definitive fixation is frequently safe, with the exception of those injuries that normally require staged management or very severe type IIIB and IIIC injuries. Traumatic wounds that can be approximated primarily should be closed at the time of initial presentation. Wounds that cannot be closed should have a negative pressure wound therapy dressing applied. The need for subsequent debridements remains a clinical judgement, but all non-viable tissue should be removed prior to definitive coverage. Cefazolin remains the standard of care for all open fractures, and type III injuries also require gram-negative coverage. Both the induced membrane technique (IMT) with staged bone grafting and distraction ostogenesis (DO) are excellent options for bony reconstruction. Soft tissue coverage within one week of injury appears critical.